Transmission of government spending shocks in the euro area: Time variation and driving forces - Markus Kirchner; Jacopo Cimadomo; Sebastian Hauptmeier (European Central Bank (ECB), 2010)
This paper provides new evidence on the effects of government spending shocks and the fiscal transmission mechanism in the euro area for the period 1980-2008. Our contribution is two-fold. First, we investigate changes in the macroeconomic impact of government spending shocks using time-varying structural VAR techniques. The results show that the short-run effectiveness of government spending in stabilizing real GDP and private consumption has increased until the end-1980s but it has decreased thereafter. Moreover, government spending multipliers at longer horizons have declined substantially over the sample period. We also observe a weaker response of real wages and a stronger response of the nominal interest rate to spending shocks. Second, we provide econometric evidence on the driving forces behind the observed time variation of spending multipliers. We find that a higher ratio of credit to households over GDP, a smaller share of government investment and a larger share of public wages over total government spending have led to decreasing contemporaneous multipliers. At the same time, our results indicate that higher government debt-to-GDP ratios have negatively affected long-term multipliers.
Keywords: C32; E62; H30; H50; 330; Fiscal transmission mechanism; Government spending shocks; Structural change; Structural vector autoregressions; Time-varying parameter models; Öffentliche Ausgaben; Schock; Geldpolitische Transmission; Strukturwandel; Bayes-Statistik; VAR-Modell; Schätzung; EU-Staaten